The role of virtual reality on physical and psychological health among older adults: A systematic review - Liao, Yeqian; Hsu, Mei Hua Kerry; Xie, Feng Ling; Dai, Hong Xia; Liu, Ming (Edelweiss Applied Science and Technology, 2024)
To synthesis and appraise the existing research about the effect and outcomes of virtual reality (VR) interventions among older adults. A systematic review. This systematic review was conducted following the PRISMA guidelines and including multiple databases: Scopus, CINHAL, PubMed, Medline, and Web of Science, from 30 March 2014 to 30 March 2024. A total of 13 studies from 424 articles were included in the review. Seven studies were randomized control trial (RCT) and five studies were quasi-experimental study for feasibility trial with one for longitudinal study. The intervention group showed positive outcomes on physical activity and cognitive function (p<0.001) among older adults. This review concluded that the use of virtual reality intervention can promote cognitive function, physical health, mental health, well-being, and reduce the risk of falls among older people. VR technology plays the role to improved physical and psychological health among older adults. Future research can study the standardized VR intervention on health promotion for the effect and sustainability among older people.